Growth hormone associated with treatment efficacy of immune checkpoint inhibitors in gastric cancer patients - Zhao, Yue; Ji, Zhengzheng; Li, Jiasong; Zhang, Shasha; Wu, Chensi; Zhang, Ruixing; Guo, Zhanjun (Frontiers in Oncology, 2022)
Background Immune checkpoint inhibitors (ICIs) combined with chemotherapy have been widely employed to improve the outcome of gastric cancer patients. In the present study, the impact of posttreatment growth hormone (GH) levels on the treatment efficacy of ICIs for advanced gastric cancer (AGC) patients was assessed. Methods Seventy-five AGC patients treated with anti-PD-1 antibodies at The Fourth Hospital of Hebei Medical University were involved. We divided AGC patients into two groups as high-GH group and low-GH group based on the GH level. Immunotherapy efficacy was assessed in terms of objective response rate, disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) based on the National Comprehensive Cancer Network Guidelines. The enumeration data were compared by χ2 test or Fisher’s exact test. Survival curves were drawn by the Kaplan–Meier method, and comparisons between the curves were made using the log-rank test. Multivariate survival analysis was performed using a Cox proportional hazards model. Results The higher GH levels were associated with a lower DCR of ICIs with a DCR of 30.0% in the high-GH group and 53.3% in the low-GH group (P = 0.046). The subsequent univariate analysis showed that a high GH level was associated with both shorter PFS (P = 0.016) and shorter OS at the borderline statistical level (P = 0.052) in AGC patients treated with ICIs. Cox model analysis also proved that the GH level was an independent risk factor for the outcome of AGC patients (PFS: P = 0.013, HR, 2.424, 95% CI, 1.202–4.890; OS: P = 0.014, HR, 3.301, 95% CI, 1.279–8.519). Conclusions The post-treatment GH level might be a predictor for ICIs treatment in AGC patients.